2001
DOI: 10.1086/323763
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of XY Sperm Increases with Age in Fathers of Boys with Klinefelter Syndrome

Abstract: With increasing availability of drugs for impotence and advanced reproductive technologies for the treatment of subfertility, more men are fathering children at advanced ages. We conducted a study of the chromosomal content of sperm of healthy men aged 24-57 years to (a) determine whether father's age was associated with increasing frequencies of aneuploid sperm including XY, disomy X, disomy Y, disomy 21, and sperm diploidy, and (b) examine the association between the frequencies of disomy 21 and sex-chromoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 43 publications
1
75
1
2
Order By: Relevance
“…Using a triple color FISH X-Y-8, we did not find a paternal age effect on sex chromosomes disomy (XX, YY, XY) in infertile patients and in donors. Our results are in accordance with the data of Bosch et al [39,40] and Luetjens et al [16], but in discordance with others studies which found an effect of age on the production of disomic sex chromosomes with varying results for XX, YY, XY [41][42][43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 84%
“…Using a triple color FISH X-Y-8, we did not find a paternal age effect on sex chromosomes disomy (XX, YY, XY) in infertile patients and in donors. Our results are in accordance with the data of Bosch et al [39,40] and Luetjens et al [16], but in discordance with others studies which found an effect of age on the production of disomic sex chromosomes with varying results for XX, YY, XY [41][42][43][44][45][46][47].…”
Section: Discussionsupporting
confidence: 84%
“…69 With regard to Klinefelter syndrome, the population risk is around 1 in 500, 72 and one study found this to be increased to 1 in 312 in men of APA .50 years old. 73 Other work has suggested that there is no significant relationship of APA with either the paternal or maternal age in Klinefelter syndrome. 1,74 An association between increased rates of cancer in children of fathers with APA has been suggested.…”
Section: Effect Of Paternal Age On Offspring Healthmentioning
confidence: 98%
“…It has been well documented that severe male infer tility correlates with a significant increase in sperm aneuploidy; in addition, other factors such as paternal age, chemotherapy treatment, smoking and alcohol have also been associated with increased sperm aneuploidy [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Given the significant increased risk of sperm aneuploidy in infertile men, concerns have been raised regarding whether these individuals are at a higher risk of giving rise to aneuploid pregnancies when treated by intracytoplasmic sperm injection (ICSI) [17].…”
Section: Introductionmentioning
confidence: 99%